PENGARUH BAHAN KEMASAN TERHADAP KUALITAS BENIH BEBERAPA VARIETAS WIJEN (Sesamum Indicum.L) - Luluk Sulistiyo Budi; Puspitawati I R; Sukarno A P; Nurwantara M P (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
The Effect of Packaging Materials On The Quality of Sesame Seed Varieties (Sesamum Indicum .L) Sesame is a plant that has high nutritional value and has a good impact on those who consume it. The success of any program to develop a commodity needs to be supported by the existence of superior varieties and quality seeds because superior varieties have been recognized as applicable, cheap, safe, environmentally friendly technology, and have high compatibility when combined with other advanced technologies. The research objective was to determine the best interaction between varieties treatment and seed packaging techniques on the quality of sesame seeds. This study used a factorial completely randomized design (CRD) consisting of 2 (two) factors and was repeated 4 (four) times. The results of the analysis showed that the interactions occurred in the germination parameters (viability) and the percentage of disease parameters. The highest viability was found in the treatment of the Sumberejo 1 sesame variety with sack packaging, and the Sumberejo 4 sesame variety with the sack package, while the lowest viability was in the treatment of the Winas 1 sesame variety with cloth packaging. The parameters of seed disease attack with the highest value were 100% in the Sumbberejo 1 variety with plastic sack packaging, the Sumberejo 2 variety with plastic sack packaging, the Sumberejo 2 variety with cloth plastic packaging, the Sumberejo 3 variety with cloth packaging, Winas 1 variety with sack packaging, and the lowest with a percentage of 0.35% in the Sumberejo 4 variety with plastic cloth packaging. This study shows that the best treatment combination is the varieties of Sumberejo 1, Sumberejo 3, and Sumberejo 4 with sack packaging. The best combination of varieties and packaging against disease is the Sumberejo 4 variety with plastic cloth packaging.Keywords: packaging, sesame seed, storage, varietiesABSTRAK Wijen merupakan tanaman yang memiliki nilai gizi tinggi dan memiliki dampak baik bagi yang mengkonsumsi. Keberhasilan setiap program pengembangan suatu komoditas perlu ditunjang adanya varietas unggul dan benih bermutu, karena varietas unggul telah diakui sebagai teknologi yang aplikatif, murah, aman, ramah lingkungan dan memiliki kompatibilitas yang tinggi bila dipadukan dengan teknologi maju lainnya. Tujuan penelitian untuk mengetahui interaksi terbaik perlakuan varietas dan teknik pengemasan benih terhadap kualitas benih tanaman wijen. Penelitian ini menggunakan rancangan acak lengkap faktorial (RAL) yang terdiri dari 2 (dua) faktor dan diulang sebanyak 4 (empat) kali. Hasil analisis menunjukkan bahwa interaksi terjadi pada paramater daya kecambah (viabilitas) dan paramater prosentase cendawan berpotensi patogen. Viabilitas tertinggi terdapat pada perlakuan varietas wijen Sumberejo 1 dengan kemasan karung, dan varietas wijen Sumberejo 4 dengan kemasan karung, sedangkan viabilitas terendah pada perlakuan varietas wijen Winas 1 dengan kemasan kain.  Parameter serangan penyakit benih dengan nilai tertinggi 100% pada varietas Sumbberejo 1 dengan kemasan plastik karung, varietas Sumberejo 2 dengan kemasan plastic karung, varietas Sumberejo 2 dengan kemasan plastic kain, varietas Sumberejo 3 dengan kemasan kain, varietas Winas 1 dengan kemasan karung, dan terendah dengan prosentase 0,35% pada varietas Sumberejo 4 dengan kemasan plastic kain.  Penelitian ini menunjukkan bahwa kombinasi perlakuan terbaik adalah varietas Sumberejo 1, Sumberejo 3, dan Sumberejo 4 dengan kemasan karung.  Kombinasi varietas dan kemasan terbaik terhadap serangan cendawan berpotensi sebagai patogen adalah varietas Sumberejo 4 dengan kemasan plastic kain. Kata Kunci: kemasan, penyimpanan, varietas, biji wijen